The Reputational Effects of Narrative Disclosures in Operational Risk Announcements - Bayley, Joel (2015)
The content of the first press cuttings regarding operational risk announcements following an operational loss event is likely to affect the level of reputational damage incurred by the institutions suffering the loss. The profile of operational risk has increased in recent decades becoming one of the major risks in the finance industry. Following increasing literature on operational events, reputational risk as a result of operational loss events has become a growing area of research. This paper analyses the content of operational loss announcements in order to assess whether the content has an effect on the level of reputational damage measured by any stock market decrease greater than the operational loss itself. Previously, content analysis has been used to assess connections between earnings and analysts’ reports however; content analysis has not previously been used to test relationships between content of operational announcements and reputational damage. This paper builds on previous reputational effect research, using content analysis as a method to provide further explanation of market overreaction known as the reputational effect. This paper does not demonstrate conclusive evidence to explain the link between the content of narrative operational loss disclosures and reputational damage however; it does establish marked areas for further research. Correspondingly, it provides evidence of the effects of specific business lines and event types that have greater negative and positive impacts on the reputational effect.